Pengaruh Indeks Pembangunan Manusia (IPM) Terhadap Pertumbuhan Ekonomi Di Provinsi Bali Tahun 2018 – 2022 - Maulana, Luai; Manulang, Imelda Beth Gracia; Pitaloka, Nur Aini; Putri, Tamia Astriyani; Maulidina, Tika; Desmawan, Deris (Universitas Maritim AMNI Semarang, 2023)
Various factors can influence a country's economic growth, among which is the availability of manpower. The substantial availability of human resources in a country can serve as a catalyst for the progress of Indonesia's economy. This research aims to determine the influence of the Human Development Index on the economic growth of Bali Province during the period of 2018-2022. The research methodology employed is quantitative, involving the gathering of data from the Central Bureau of Statistics (BPS) and a literature review. In this study, the dependent variable is Economic Growth, while the independent variable is the Human Development Index (HDI). The research findings reveal that the HDI has no significant impact on economic growth.